114k views
4 votes
Solve.

{y=x−63x+2y=8

Use the substitution method.

Write your answer as a coordinate point (x,y).

User Jaredzhang
by
4.1k points

1 Answer

4 votes
r Answer:
( 4, -2)

Explanation:
{y=x-6
{3x+2y=8

You already have y as your first equation's subject. So, use the content from the y equation and substitute it into the second equation. Then you get,

3x+2(x-6)=8

Solve it like a normal equation for the unknown.

3x+2x-12=8
5x-12=8
5x=20
x=4

Now, substitue the new x we got into the first equation.

y=x-6
y=4-6
y=-2

User Nimey Sara Thomas
by
5.0k points